Effect of Potting Media on Growth, Flowering and Bulb Production of Hippeastrum (Hippeastrum hybridum Hort.) - Jamil, Md. Khalid; Rahman, M. Mizanur; Hossain, M. Mofazzal; Hossain, M. Tofazzal; Karim, A.J.M. Sirajul (International Journal of Applied Sciences and Biotechnology, 2016)
A pot experiment was conducted at the Horticulture Research Farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur-1706, during the period from March, 2008 to May, 2009 to investigate the suitable potting media for flower and bulb production of hippeastrum. The potting media containing a mixture of rice husk and cowdung at the ratio of 1:1 supplemented with 10 g per pot (30 cm) each of TSP and MP was found to be the best for bigger size of flower (14.20 x 13.70 cm) and flower scape (44.40 x 27.30 cm), the highest number (7.4) and weight (252.5 g) of bulblets, the maximum diameter (76.0 mm) and weight (218.4 g) of mother bulb and total bulb yield (470.9 g) of hippeastrum. But the maximum number (3.8) of flower per scape and the longest flowering duration (11.60 days) were obtained from the potting media containing a mixture of soil, rice husk, cowdung and coirdust in 1:1:1:1 ratio supplemented with 10 g each of TSP and MP. Int J Appl Sci Biotechnol, Vol 4(3): 259-271